2015
DOI: 10.1111/iwj.12389
|View full text |Cite
|
Sign up to set email alerts
|

Non‐contact low‐frequency ultrasound therapy compared with UK standard of care for venous leg ulcers: a single‐centre, assessor‐blinded, randomised controlled trial

Abstract: Abstract'Hard-to-heal' wounds are those which fail to heal with standard therapy in an orderly and timely manner and may warrant the use of advanced treatments such as non-contact low-frequency ultrasound (NLFU) therapy. This evaluator-blinded, single-site, randomised controlled trial, compared NLFU in addition to UK standard of care [SOC: (NLFU + SOC)] three times a week, with SOC alone at least once a week. Patients with chronic venous leg ulcers were eligible to participate. All 36 randomised patients compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…CVLUs epitomize a dreaded complication of chronic venous disease including superficial and deep venous hypertension, reflux, and insufficiency. Patients with CVLUs have a substantially poorer QoL due to the associated pain, odor, and reduced mobility . The onset of infection may further delay the healing process in such lesions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CVLUs epitomize a dreaded complication of chronic venous disease including superficial and deep venous hypertension, reflux, and insufficiency. Patients with CVLUs have a substantially poorer QoL due to the associated pain, odor, and reduced mobility . The onset of infection may further delay the healing process in such lesions .…”
Section: Discussionmentioning
confidence: 99%
“…Noncontact low‐frequency ultrasound (NLFU) has been used to treat various types of chronic wounds including diabetic and pressure ulcers as well as venous leg ulcers . The NLFU system uses continuous ultrasonic energy to atomize saline and deliver continuous energy to the treatment site.…”
mentioning
confidence: 99%
“…24 Experience derived from daily clinical practice of wound therapy has shown that removal of necrotic or devitalized tissue is perhaps the most important part of local wound treatment and minimizes the bioburden of wounds by decreasing the presence of bacteria, reducing the hypoxic part of the wound, and diminishing the local inflammatory reaction. 17 Extensive and detailed wound assessment at patient's admission is a prerequisite for determining appropriate treatment pathway to be followed.…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49][50][51][52][53][54][55][56][57] Six of the studies were randomized controlled trials, 47,50,52,54,55,57 two studies were placebocontrolled (mock intervention used) trials, 48,49 one study was a retrospective analysis/case series, 53 one study was a comparative analysis 54 and one study was a non-comparative analysis. 51 Four studies examined venous ulcers, 49,[55][56][57] five studies examined chronic leg ulcers 47,48,51,53 with one study that included individuals that also had critical limb ischemia, 52 one study examined DFUs 50 and one study examined pressure ulcers. 54 Only two studies 47,48 reported no significant differences in any measured dependent variable.…”
Section: Original Studies Of the Effectiveness Of Therapeutic Ultrasoundmentioning
confidence: 99%
“…White et al 57 in a single-site, evaluator-blinded randomized control trial SOC therapy delivered at least once weakly with NCLFU plus SOC therapy on change in wound area, quality of life (QoL) scores, pain scores and infection numbers. Wound area decreased by 47% in the SOC-NCLFU treatment group versus 39% reduction in the SOC therapyonly treatment group.…”
mentioning
confidence: 99%